Family and Kinship in Early Modern German Prose Novels. (October 2015) - Classen, Albrecht
<x xml:space="preserve">Abstract</x> The debate about the relevance of the marriage theme in the late Middle Ages has been ongoing for a long time. We are still collecting data to establish a solid paradigm for future discussions about this topic. The current article examines two highly popular prose novels, Thüring von Ringoltingen's Melusine (1456) and the anonymous Fortunatus (1509) where the married life of the protagonist gains much more traction in the narrative development than in previous courtly romances. Most importantly, both authors place significant emphasis on the role of the family and portray their characters as situated in the network of smaller social units consisting of parents and children only. We can thus recognize the meaningfulness of the new genre of the prose novel (Volksbuch) in the public discourse about family and kinship during the late Middle Ages.